Prevalencia de deformidad septal según hallazgos endoscópicos de la clasificación Mladina en el Hospital Regional de Trujillo - Carita Cansaya, Nimer Esmelin (2019)
Objective: To determine the prevalence of septal deformity according to endoscopic findings of the Mladina classification in adult patients of the Regional Hospital of Trujillo Material and Methods: It is a descriptive, non-experimental, prospective design of patients diagnosed with septal deformity treated in Otorhinolaryngology Outpatient Clinics in the Regional Teaching Hospital of Trujillo, after being identified, they will be programmed for endoscopic ambulatory study in endoscopic surgery; to specify the type of septal deformity; until completing the required sample size, by simple random sampling. The type of septal deviation will be determined, the presence of intervening variables (age, sex and clinical origin) will be specified in the corresponding data collection sheet, for their respective analysis.